An Implementation of Teacher Pedagogy on Students’ Biology Learning Outcomes at SMAN Bukit Sundi, Solok District - Sari, Rahmi Septia; Lufri, Lufri; Darmansyah, Darmansyah; Purnamasari, Lora (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
This research started from the problem of low student learning outcomes on the virus learning material, evidenced by the below-standard quiz scores. Therefore, the learning outcomes were not as expected. This research aims to know the implementation of biology learning in senior high school, which includes the design, implementation, and assessment of learning. The research informants were teachers of biology and Senior high school students. This type of research is descriptive with a qualitative approach. Based on the findings, it can be concluded that (1) the teachers are not contextually planning the learning. (2) The teachers are not effectively and efficiently implementing the learning due to (a) the lack of effective time utilization, (b) the lack of ability to establish and select instructional media appropriate to the criteria of the learning material, and (c) the poor quality of laboratory equipment. (3) The teachers assess student learning outcomes despite the incorrect procedures. ABSTRAK: Penelitian ini berawal dari permasalahan rendahnya hasil belajar siswa. Hal ini terbukti dari hasil kuis siswa yang berada dibawah (KKM) sehingga nilai Biologi tidak sesuai yang diharapkan. Penelitian ini bertujuan untuk mengetahui implementasi Pedagogik guru dan hasil pembelajaran biologi di SMAN Bukit sundi yang meliputi implementasi dan penilaian hasil pembelajaran. Informan dalam penelitian ini adalah guru biologi, siswa kelas X. Jenis penelitian deskriptif dengan pendekatan kualitatif. Berdasarkan temuan hasil penelitian tersebutterlihat (1) Guru tidak merencanakan pembelajaran secara kontekstual dengan konteks pembelajaran dilaksanakan. (2) Guru yang menerapkan pembelajaran belum efektif dan efisien karena: (a) Guru belum memanfaatkan waktu secara efektif, (b) Guru belum dapat menetapkan dan memilih media pembelajaran (c) pembelajaran belum efektif karena terbatasnya peralatan laboratorium. (3) Guru melakukan penilaian hasil belajar dengan prosedur yang belum tepat.